LIN28A inhibits DUSP family phosphatases and activates MAPK signaling pathway to maintain pluripotency in porcine induced pluripotent stem cells - Wu, Xiao-Long (Science Press, 2021)

(untitled) (Zool Res)
LIN28A, an RNA-binding protein, plays an important role in porcine induced pluripotent stem cells (piPSCs). However, the molecular mechanism underlying the function of LIN28A in the maintenance of pluripotency in piPSCs remains unclear. Here, we explored the function of LIN28A in piPSCs based on its overexpression and knockdown. We performed total RNA sequencing (RNA-seq) of piPSCs and detected the expression levels of relevant genes by quantitative real-time polymerase chain reaction (qRT-PCR), western blot analysis, and immunofluorescence staining. Results indicated that piPSC proliferation ability decreased following LIN28A knockdown. Furthermore, when LIN28A expression in the shLIN28A2 group was lower (by 20%) than that in the negative control knockdown group (shNC), the pluripotency of piPSCs disappeared and they differentiated into neuroectoderm cells. Results also showed that LIN28A overexpression inhibited the expression of DUSP (dual-specificity phosphatases) family phosphatases and activated the mitogen-activated protein kinase (MAPK) signaling pathway. Thus, LIN28A appears to activate the MAPK signaling pathway to maintain the pluripotency and proliferation ability of piPSCs. Our study provides a new resource for exploring the functions of LIN28A in piPSCs.